Relationship between cerebral venous sinus thrombosis and intracranial arteritis during pregnancy and post partum. (October 2021) - Li, Xiurong; Dong, Jianan; Sun, Yaping; Li, Qing; Shi, Li
Our study was conducted to explore the relationship between cerebral venous sinus thrombosis (CVST) and intracranial arteritis during the time of pregnancy as well as puerperium. The current retrospective case study involved a total of 153 patients with pregnancy-related CVST. CVST was diagnosed mainly based on clinical manifestations and imaging results. Detailed information on demographics, risk factors (excluding intracranial arteritis), and pregnancy outcomes was systematically recorded. The average age of patients diagnosed with CVST was 28.67±3.54 years old. Among these patients, there were 62 cases of puerperal CVST and 91 cases of pregnancy-related CVST. The clinical manifestations of patients with CVST included headache in 55 cases (35.95%), symptomatic seizures in 26 cases (16.99%), symptomatic limb weakness in 22 cases (14.38%), symptomatic nausea/vomiting in 18 cases (11.76%), symptomatic disturbance of consciousness in 15 cases (9.80%), symptomatic blurred vision in 10 cases (6.54%), and symptomatic fever in 7 cases (4.58%). A proportion of patients reported higher abnormal cerebrospinal fluid pressure (98.28%), white cell count (79.31%), total cholesterol (71.55%) and low-density lipoprotein (62.93%) (p<0.01). The proportion of intracranial arteritis lesions and CVST lesions was high, including 51 cases (43.97%) on the left side and 31 cases (26.72%) on the right side. Bilateral CVST lesions occurred in 13 cases (11.20%) of unilateral intracranial arteritis lesions, and bilateral intracranial arteritis lesions occurred in 16 cases (13.79%) of unilateral CVST lesions. In summary, CVST indicates a potential positive link to intracranial arteritis at the time of pregnancy and puerperium.